Differential regulation of blood flow induced neovascularisation and mural cell recruitment by VEGF and angiopoietin signaling - Stone, Oliver A.; Carter, James G.; Lin, P. Charles; Paleolog, Maria J.C.; Bates, David O. (Wiley, 2017)
Signalling through VEGF receptors and the Tie2 receptor by angiopoietins is required in combination with blood flow for the formation of a functional vascular network. We tested the hypothesis that VEGF and Ang1 contribute differentially to neovascularization induced by nitric oxide (NO) mediated vasodilatation, by comparing the phenotype of new microvessels in the mesentery during induction of vascular remodeling by over-expression of endothelial nitric oxide synthase (eNOS) in the fat pad of the adult rat mesentery during inhibition of Angiopoietin signalling with soluble Tie2 and VEGF signalling with sFlt1. We find that NO mediated angiogenesis was blocked by inhibition of VEGF with sFlt1 (from 881±98% increase in functional vessel area (FVA) to 279±72%) and by inhibition of angiopoietin with soluble Tie2 (to 337±67%). Exogenous angiopoietin-1 was required to induce arteriolargenesis (8.6±1.3% of vessels with recruitment of vascular smooth muscle cells, VSMC) in the presence of enhanced flow. Soluble Tie2 and sFlt1 both inhibited VSMC recruitment (both 0%), and VEGF inhibition increased pericyte recruitment to newly formed vessels (from 27±2 to 54±3% pericyte ensheathment). We demonstrate that a fine balance of VEGF and Angiopoietin signaling is required for the formation of a functional vascular network. Endogenous VEGF signaling prevents excess neovessel pericyte coverage, and is required for VSMC recruitment during increased nitric oxide mediated vasodilatation and angiopoietin signalling (NO-Tie mediated arteriogenesis). Therapeutic vascular remodeling paradigms may therefore require treatments that modulate blood flow to utilise endogenous VEGF, in combination with exogenous Ang1, for effective neovascularisation.